Examining Interaction in Synchronous Online Classes: Voices From Vietnamese Tertiary Students - Duong Minh Tuan; Le Thi Diem Lan (SAGE Open)
This study scrutinized Vietnamese university students’ perceptions of their interaction in synchronous online classes. With a mixed-methods design, the study integrated quantitative and qualitative approaches. The participants comprised 200 tertiary students at a private university in the Mekong Delta of Vietnam. Data were gathered through a survey questionnaire and focus group interviews. The results revealed that students obtained a moderate level of interaction in online classes, with student–content and student–interface interactions being perceived as equally the most common. This was followed by student–teacher interaction, whereas student–student interaction was cited to be the least frequent. Qualitative analysis elucidated nuanced perceptions, with discernible disparities between the two groups of participants having higher and lower interaction levels. The former expressed confidence in digital platform usage, emphasizing technological proficiency’s significance, while the latter encountered challenges and lacked confidence in platform utilization. Both groups recognized the importance of engaging with course materials but differed in their perceptions of volume and learning facilitation. Despite frequent student–teacher interactions, face-to-face learning was preferred due to perceived detachment in online learning environments. Peer interaction, particularly deficient in the lower interaction group, underscored challenges in online collaborative activities.